If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(3x + 2) = 11 Reorder the terms: 5x + -1(2 + 3x) = 11 5x + (2 * -1 + 3x * -1) = 11 5x + (-2 + -3x) = 11 Reorder the terms: -2 + 5x + -3x = 11 Combine like terms: 5x + -3x = 2x -2 + 2x = 11 Solving -2 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 11 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 11 + 2 2x = 11 + 2 Combine like terms: 11 + 2 = 13 2x = 13 Divide each side by '2'. x = 6.5 Simplifying x = 6.5
| -6-4x=10 | | 15-(3x+1)=2x | | 3-13=102 | | y-6= | | -8x-44=-20x+14 | | x-16=47 | | 7n=4200 | | f(x)=x^2+9x+18 | | y-5=(x-1) | | -5a+7.5=-17.5 | | y^2-22y+121= | | 5x=-8x-5 | | -17.5=-5+7.5 | | (2x+5)=(6x+15) | | -1-2h=43 | | 9d-5=4d+35 | | 790/820 | | q-13=13 | | 3/4=21/2+d | | y:2=35 | | -x+4x+6=11 | | 6-8x-3x= | | k/2-3/5=3x-2/5 | | -5x+12x-8=0 | | 6X-3X=-4+8 | | x^2+15xy+44y^2= | | C=8.5x+6(7) | | 3i/1+i=0 | | 7-3m=-26 | | -5n-6n=11 | | 11c-12=7c+24 | | -7x+4y=-15 |